Engineering of Bioresorbable Polymers for Tissue Engineering and Drug Delivery Applications - Dobrzyńska-Mizera, Monika; Dodda, Jagan Mohan; Liu, Xiaohua; Knitter, Monika; Oosterbeek, Reece N; Salinas, Pablo; Pozo, Eduardo; Ferreira, Ana Marina; Sadiku, Emmanuel Rotimi (Advanced healthcare materials, 2024)
Herein, the recent advances in the development of resorbable polymeric-based biomaterials, their geometrical forms, resorption mechanisms, and their capabilities in various biomedical applications are critically reviewed. A comprehensive discussion of the engineering approaches for the fabrication of polymeric resorbable scaffolds for tissue engineering, drug delivery, surgical, cardiological, aesthetical, dental and cardiovascular applications, are also explained. Furthermore, to understand the internal structures of resorbable scaffolds, representative studies of their evaluation by medical imaging techniques, e.g., cardiac computer tomography, are succinctly highlighted. This approach provides crucial clinical insights which help to improve the materials' suitable and viable characteristics for them to meet the highly restrictive medical requirements. Finally, the aspects of the legal regulations and the associated challenges in translating research into desirable clinical and marketable materials of polymeric-based formulations, are presented.
Keywords: Tissue Engineering; drug delivery; resorbable biomaterials; medical imaging; polymer matrices; Absorbable Implants; Polymers; tissue engineering; tkáňové inženýrství; clinical challenges; Drug Delivery Systems; Animals; lidé; biokompatibilní materiály; polymery; Humans; zvířata; Tissue Scaffolds; tkáňové podpůrné struktury; implants; vstřebatelné implantáty; Biocompatible Materials; lékové transportní systémy